Royale with cheese: The effect of globalization on the variety of goods - Matthew T. Cole; Ronald B. Davies (University College Dublin, UCD School of Economics, 2010)
The key result of the so-called New Trade Theory is that countries gain from falling trade costs by an increase in the number of varieties available to consumers. Though the number of varieties in a given country rises, it is also true that global variety decreases from increased competition wherein imported varieties drive out some local varieties. This second result is a major issue for anti-trade activists who criticize the move towards free trade as promoting homogenization or Americanization of varieties across countries. We present a model of endogenous entry with heterogeneous firms which models this concern in two ways: a portion of a consumer's income is spent overseas (i.e. tourism) and an existence value (a common tool in environmental economics where simply knowing that a species exists provides utility). Since lowering trade costs induces additional varieties to export and drives out some non-exported varieties, these modifications result in welfare losses not accounted for in the existing literature. Nevertheless, it is only through the existence value that welfare can fall as a result of declining trade barriers. Thus, for these criticisms of globalization to dominate, it must be that this loss in the existence value outweighs the direct benefits from consumption.
hdl:10197/2657
Keywords: F10; F12; F13; 330; Trade theory; Globalization; Variety; Tourism